Do czego konieczny jest język? Co jest konieczne w języku? - Danielewiczowa, Magdalena (Załącznik Kulturoznawczy, 2023)
The article attempts to answer two closely interrelated questions: What is a natural language necessary for and, on the other hand, what is necessary in the language itself? In the first part the author puts forward a thesis that there is a gulf between human speech and animal codes − a gulf which cannot be filled with explanations of evolutionary nature. She also invokes a series of ideas of distinguished scholars who advocate the logical primacy of language in relation to all other semiotic systems that create the space of culture. In the second part of the article, the inalienable properties of language are discussed, those that determine its essence and, at the same time, the uniqueness with respect to both the animal signals and all other sign systems. These features include: double demarcation, duality, proportionality, the possession of reference and predictive expressions, metalinguistic and metatextual tools, as well as tools for communicating the truth and knowledge of the world.